2019
DOI: 10.1093/pcp/pcz024
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of sun, ovate, fs8.1 and Auxin Application on Tomato Fruit Shape and Gene Expression

Abstract: Elongated tomato fruit shape is the result of the action of the fruit shape genes possibly in coordination with the phytohormone auxin. To investigate the possible link between auxin and the fruit shape genes, a series of auxin (2,4-D) treatments were performed on the wild-type and the fruit shape nearisogenic lines (NILs) in Solanum pimpinellifolium accession LA1589 background. Morphological and histological analyses indicated that auxin application approximately 3 weeks before anthesis led to elongated pear-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…We also detected the upregulated expression of auxin-related genes. These genes may be involved in fruit elongation, as many studies have shown that phytohormones, especially auxin and gibberellins, are related to fruit growth and changes in fruit shape 55 . These results are consistent with those of previous studies that found that three homologs of auxin-related genes were differentially expressed in developing watermelon fruits 54 .…”
Section: Discussionmentioning
confidence: 99%
“…We also detected the upregulated expression of auxin-related genes. These genes may be involved in fruit elongation, as many studies have shown that phytohormones, especially auxin and gibberellins, are related to fruit growth and changes in fruit shape 55 . These results are consistent with those of previous studies that found that three homologs of auxin-related genes were differentially expressed in developing watermelon fruits 54 .…”
Section: Discussionmentioning
confidence: 99%
“…A mutation in the FW2.2 promoter inhibits cell division during flower development and causes a larger fruit phenotype [15]. Another gene SUN1 encodes a protein harboring an IQ67 domain and affects cell number along the entire proximal-distal axis, resulting in fruit elongation [16,17,18]. OVATE family proteins (OFPs) and TONNEAU1 Recruiting Motif proteins affect fruit shape by regulating cell division patterns during ovary development [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…SUN has a stronger effect on transcriptome than OVATE and fs8.1 . Auxin has been implicated in regulating the expression of some of the fruit shape genes [18], but little is known about other molecules that may affect fruit size and shape.…”
Section: Introductionmentioning
confidence: 99%
“…Auxin is involved in the regulation of cell wall loosening and cell elongation ( Majda and Robert, 2018 ; Wang et al, 2019 ). Eight genes associated with auxin signaling were differentially expressed between the bulks, mostly upregulated in the round-fruited bulk.…”
Section: Resultsmentioning
confidence: 99%